2008
DOI: 10.1016/j.neuroscience.2007.10.064
|View full text |Cite
|
Sign up to set email alerts
|

The role of transcription factors cyclic-AMP responsive element modulator (CREM) and inducible cyclic-AMP early repressor (ICER) in epileptogenesis

Abstract: Alterations in the brain that contribute to the development of epilepsy, also called epileptogenesis, are not well understood, which makes it difficult to develop strategies for preventing epilepsy. Here we have studied the role of the CRE binding transcription factors, cyclic-AMP responsive element modulator (CREM) and inducible cyclic-AMP early repressor (ICER), in the development of epilepsy following pilocarpine induced status epilepticus (SE) in mice. Following SE, ICER mRNA and protein are increased in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…These results strongly suggest that ICER plays significant roles in this type of neuronal plasticity. This is further supported by recent findings that CREM/ICER null mutant mice have higher frequency of spontaneous seizures after pilocarpine-induced status epilepticus (Porter et al, 2008). The increased ICER levels in ICER-OE mice may retard kindling by attenuating and "localizing" hyperexcitation, which results as a consequence of day-to-day restriction of excessive gene transcription during kindling.…”
Section: Negative Regulation Of Kindling Epileptogenesis By Icersupporting
confidence: 72%
See 1 more Smart Citation
“…These results strongly suggest that ICER plays significant roles in this type of neuronal plasticity. This is further supported by recent findings that CREM/ICER null mutant mice have higher frequency of spontaneous seizures after pilocarpine-induced status epilepticus (Porter et al, 2008). The increased ICER levels in ICER-OE mice may retard kindling by attenuating and "localizing" hyperexcitation, which results as a consequence of day-to-day restriction of excessive gene transcription during kindling.…”
Section: Negative Regulation Of Kindling Epileptogenesis By Icersupporting
confidence: 72%
“…1 B, C, available at www.jneurosci.org as supplemental material). Similarly, an increase in ICER mRNAs was found in the hippocampus, as well as other brain regions in response to seizures evoked by electroconvulsive shock (RydelekFitzgerald et al, 1996), kainite (Konopka et al, 1998), and pilocarpine (Porter et al, 2008). To study the relationship between ICER upregulation and downregulation and epileptogenesis, we examined kindling development in ICER-OE mice (lines I-15…”
Section: Odor Discrimination Memory Is Not Affected In Icer Mutant Micementioning
confidence: 99%
“…These results are consistent with microarray data showing that CREB promotes the transcription of the 1b sodium channel subunit while decreasing the expression of K V 1.4 potassium channel subunit (120). In addition to its role in the modulation of intrinsic neuronal excitability, altered regulation of CREB signaling could also be a factor underlying CNS disorders including epilepsy (121,122) and depression-like behaviors (120). For example, mice expressing the artificial CREB inhibitor A-CREB were resistant to two common models of epilepsy (including kindling), whereas mice that have CREB regulators ICER and/or CREM knocked out (122) or absent (121) showed accelerated kindling and greater probability of spontaneous seizures after status epilepticus (121).…”
Section: Molecular Substrates Of Intrinsic Neuronal Excitabilitysupporting
confidence: 90%
“…In addition to its role in the modulation of intrinsic neuronal excitability, altered regulation of CREB signaling could also be a factor underlying CNS disorders including epilepsy (121,122) and depression-like behaviors (120). For example, mice expressing the artificial CREB inhibitor A-CREB were resistant to two common models of epilepsy (including kindling), whereas mice that have CREB regulators ICER and/or CREM knocked out (122) or absent (121) showed accelerated kindling and greater probability of spontaneous seizures after status epilepticus (121). Taken together, these results suggest that a major function of CREB in the CNS is the modulation of intrinsic neuronal excitability, and that disruption of CREB signaling could be a common underlying mechanism contributing to several disorders of the CNS.…”
Section: Molecular Substrates Of Intrinsic Neuronal Excitabilitymentioning
confidence: 99%
“…Interesting candidates are transcription factors, which can control expression of many genes. For example, inducible cAMP early repressor (ICER) has been suggested to play a role in epileptogenesis as it suppresses kindling (Kojima et al 2008;Porter et al 2008). Other candidates include cAMP response element (CREB), controlling differential expression of genes in human epileptic cortex (Beaumont et al 2012), and repressor element-1 silencing transcription factor (NRSF) shown to repress epileptogenesis in a kindling model and reported to regulate target genes relevant for neuronal network remodeling in kainate-induced SE (Hu et al 2011;McClelland et al 2014).…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%